Hubungan Antara Durasi Penggunaan Smartphone Dan Keluhan Nyeri Leher Pada Tim E-Sport Mobile Legend - Arthamevia, Sheilla Maurie; Bachtiar, Farahdina; Prabowo, Eko; Purnamadyawati, Purnamadyawati (Jurnal Fisioterapi Terapan Indonesia, 2022)
Smartphones are a real manifestation of technological progress as well as a device that works very complexly with access to the internet, social media and games. E-sports or cybersports connected to the internet network. Excessive use of smartphones, including for Mobile Legends E-sports players, can cause musculoskeletal disorders. Musculoskeletal disorders associated with smartphone use lead to neck muscle fatigue caused by poor posture. Using a smartphone for a long time can cause muscle tension. Long duration of smartphone use is the biggest factor that can cause complaints of neck pain. Purpose: This study aims to determine the relationship between the duration of smartphone use and neck pain in Mobile Legends players on the E-sport team at UPN Veteran Jakarta. Methods: The research design is a correlational study with a cross-sectional approach. Data collection was conducted using a questionnaire. Pain was measured using the NRS (Numeric Rating Scale). Results: Based on the results of statistical tests using SPSS 25.0, it was found that p = 0,002 or p < 0,05. The Pearson correlation coefficient for NRS was r = 1.0 and the duration of smartphone use was r = 0.341. Conclusion: There is a significant relationship between the duration of smartphone use and neck pain with a weak relationship level.